Digital PID controllers with fractional variable order techniques and two discrete-time operator variants - Mozyrska, Dorota; Wyrwas, Malgorzata; Oziablo, Piotr (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
This paper introduces a control strategy utilizing the fractional variable order PID digital controller (FVOPID). We employ two variants of fractional discrete-time operators with variable order: the Grünwald-Letnikov type and its convolution version. We examine and compare the performance of both controllers types on a higher-order plant. Parameter optimization is conducted using a particle swarm algorithm.